Comparative Static Analysis in Reinforced Concrete Superstructure Beams: Working Stress vs. Limit State Approaches - Trung, Hieu Tran; Vuong, Pham Ngoc; Van, Tran Thi Thuy (Engineering, Technology & Applied Science Research, 2025)
Historically, the design and analysis of bridge superstructures in Russia and Vietnam were based on standardized schemes utilizing the Working Stress Method (WSM). Although effective in its time, WSM is now considered outdated due to its conservative assumptions and limited ability to capture the actual performance of structural materials. With the advancement of structural design standards, the Limit State Method (LSM) has become the preferred analytical approach, offering a more realistic and comprehensive assessment of structural behavior. This study presents a comparative analysis of WSM and LSM applied to the static analysis of Reinforced Concrete beams in bridge superstructures. By recalculating existing components using LSM, the results indicate a significant reserve in load-bearing capacity, with an increase of approximately 30–32% for moving loads under the AK and NK loading schemes, values typically underestimated by WSM. These findings help explain the continued satisfactory performance of many aging bridge structures, originally designed for lower load classes, in meeting contemporary traffic demands.